1990
DOI: 10.1113/jphysiol.1990.sp018128
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression by nerve growth factor of two types of Ca2+ channels in rat phaeochromocytoma cell lines.

Abstract: SUMMARY1. Two clones of rat phaeochromocytoma PC12 cells have been used to study the expression of Ca2+ channels and their possible involvement in neuronal differentiation. One clone differentiated morphologically when exposed to nerve growth factor (NGF) for 4 days (PC12 cells), while the other clone was insensitive to NGF, but differentiated morphologically in the presence of ouabain (041 mM

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
110
3

Year Published

1993
1993
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(140 citation statements)
references
References 36 publications
27
110
3
Order By: Relevance
“…1C shows a representative example of Ca 2ϩ current recorded in a PC12 cell during a depolarizing pulse to ϩ20 mV followed by repolarization to Ϫ70 mV. Consistent with other analyses on Ca 2ϩ currents in PC12 cells (28,29), the recorded current appeared to result predominantly from the expression of HVA and fast deactivating channels, as evidenced by the fast tail current generated when the membrane was repolarized to Ϫ70 mV. The apparent activation threshold of the whole cell Ca 2ϩ current in PC12 cells was observed at about Ϫ50 mV, and maximal current amplitude was observed at ϩ20 mV (see below).…”
Section: Identification Of T-type Ca 2ϩ Channels In Pc12 Cells-pc12supporting
confidence: 65%
See 2 more Smart Citations
“…1C shows a representative example of Ca 2ϩ current recorded in a PC12 cell during a depolarizing pulse to ϩ20 mV followed by repolarization to Ϫ70 mV. Consistent with other analyses on Ca 2ϩ currents in PC12 cells (28,29), the recorded current appeared to result predominantly from the expression of HVA and fast deactivating channels, as evidenced by the fast tail current generated when the membrane was repolarized to Ϫ70 mV. The apparent activation threshold of the whole cell Ca 2ϩ current in PC12 cells was observed at about Ϫ50 mV, and maximal current amplitude was observed at ϩ20 mV (see below).…”
Section: Identification Of T-type Ca 2ϩ Channels In Pc12 Cells-pc12supporting
confidence: 65%
“…are chromaffin-like cells that express HVA Ca 2ϩ channels, which have been identified by biophysical and molecular approaches as L-, N-, and P/Q-subtypes (28,29). To our knowledge, T-type Ca 2ϩ channels have not previously been reported in quiescent PC12 cells.…”
Section: Identification Of T-type Ca 2ϩ Channels In Pc12 Cells-pc12mentioning
confidence: 98%
See 1 more Smart Citation
“…NGF-differentiated PC12 cells have been demonstrated to possess L-type (dihydropyridine sensitive) and N-type (ω-conotoxin-GIVa sensitive) voltage-dependent Ca 2+ channels [21,22,27,28]. D 2 receptor activation has been shown to block various calcium channels [29][30][31][32].…”
Section: A Pertussis Toxin Sensitive and Voltage-dependent Calcium Chmentioning
confidence: 99%
“…8A]. According to previous studies (15)(16)(17), we found that the whole-cell Ca 2ϩ currents in naïve cells were comprised of low-voltage activated (LVA) and high voltage activated (HVA) conductances (Fig. 1 A).…”
Section: Il1rapl1 Induces a Specific Reduction In Amplitude Of High-vmentioning
confidence: 99%